First principles calculations on the origin of violet-blue and green light photoluminescence emission in SrZrO3 and SrTiO3 perovskites - Longo, Valeria M. [UNESP]; Cavalcante, Laecio S.; Costa, Maria G. S. [UNESP]; Moreira, Mario Lucio; de Figueiredo, Alberthmeiry T. [UNESP]; Andres, Juan; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer, 2009)
The photoluminescence (PL) emission from SrZrO3 (SZ) and SrTiO3 (ST) crystalline, quasi-crystalline, and quasi-amorphous samples, prepared by the polymeric precursor method, was examined by ab initio quantum mechanical calculations. It was used in the modeling the structural model consisting of one pyramidal TiO5 or ZrO5 unit piled upon the TiO6 or ZrO6, which are representative of disordered structures of quasi-crystalline structures such as ST and SZ. The structural crystallization process was monitored by X-ray diffraction. In quasi-crystalline powders, the photoluminescence (PL) in the visible region showed different peak positions and intensities in SZ and ST. The PL emission was linked to distinct distortions in perovskite lattices and the emission of two colors-violet-blue in SZ and green in ST-was also examined in the light of favorable structural and electronic conditions.
Keywords: Ab initio calculations; Perosvskite; Photoluminescence